2002
DOI: 10.1007/s00442-002-0964-y
|View full text |Cite
|
Sign up to set email alerts
|

Supply and demand processes as controls over needle monoterpene synthesis and concentration in Douglas fir [Pseudotsuga menziesii (Mirb.) Franco]

Abstract: We measured the relative control that resource availability (as a supply-side control) and wounding (as a demand-side control) exert on patterns of monoterpene synthesis and concentration in Douglas fir [Pseudotsuga menziesii (Mirb.) Franco] needles. While supply-side controls should alter monoterpene production due to changes in the availability of substrate (carbohydrates), demand-side controls alter the need for a defensive product. We examined these relationships by measuring constitutive (preformed) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 48 publications
8
28
1
Order By: Relevance
“…0.2-0.8% of needle dry weight. These 10 concentrations are in a similar range to previous observations from other conifers (Lerdau et al, 1997;Litvak and Monson, 1998;Litvak et al, 2002;Kännaste et al, 2013). Since emissions were three orders of magnitude less than pool sizes, they are unlikely to affect the pool sizes in the short to medium term.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…0.2-0.8% of needle dry weight. These 10 concentrations are in a similar range to previous observations from other conifers (Lerdau et al, 1997;Litvak and Monson, 1998;Litvak et al, 2002;Kännaste et al, 2013). Since emissions were three orders of magnitude less than pool sizes, they are unlikely to affect the pool sizes in the short to medium term.…”
Section: Discussionsupporting
confidence: 86%
“…or three other Mediterranean woody plants in response to drought and warming (Llusià et al, 2006). Litvak et al (2002) found no relationship between monoterpene storage pool sizes and synthase activities of Douglas fir (Pseudotsuga menziesii). Therefore, a reasonable question is how the phenology, seasonality and environmental stimuli affect 15 the production, storage and emission of monoterpenes, and to what extent they are interrelated.…”
Section: Introductionmentioning
confidence: 85%
“…Due to the high K m value of isoprene synthase, poor substrate availability due to partitioning to competing pathways may prevent isoprene synthase to be active. Even though it is questionable whether isoprenoid synthesis is ever limited by photosynthesis, as isoprenoid synthesis requires only a few percent of total photosynthetic turnover of reduced carbon, ATP and NADPH (Niinemets et al 2002b), this physiological regulation of isoprene biosynthesis would be consistent with the Carbon-Nutrient Balance Hypothesis (CNB) and/or the Growth-Differentiation Balance Hypothesis (GDB) (Litvak, Constable & Monson 2002). CNB and GDB assume that the synthesis of carbon-rich secondary compounds is limited by the availability of photosynthates (i.e.…”
Section: Link Between Isoprene Emission Capacity and Gross Photosynthmentioning
confidence: 86%
“…Theoretical considerations based on tissue carbon/nitrogen (C/N) ratios predict stronger accumulation of secondary compounds such as monoterpenes when carbon availability is in excess of that required for growth, e.g., under elevated CO 2 concentrations (Lerdau et al, 1994;Litvak et al, 2002;Peñuelas and Estiarte, 1998). This in turn suggests potentially higher emissions under elevated CO 2 (Lerdau et al, 1994;Litvak et al, 2002;Peñuelas and Estiarte, 1998).…”
Section: Growth Co 2 Effects In Terpene-storing Speciesmentioning
confidence: 99%